2013
DOI: 10.1088/0034-4885/76/4/046602
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous transport in the crowded world of biological cells

Abstract: A ubiquitous observation in cell biology is that the diffusive motion of macromolecules and organelles is anomalous, and a description simply based on the conventional diffusion equation with diffusion constants measured in dilute solution fails. This is commonly attributed to macromolecular crowding in the interior of cells and in cellular membranes, summarising their densely packed and heterogeneous structures. The most familiar phenomenon is a sublinear, power-law increase of the mean-square displacement as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,254
4
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,163 publications
(1,297 citation statements)
references
References 338 publications
(750 reference statements)
32
1,254
4
7
Order By: Relevance
“…To further explore the discrepancy in anomalous exponent uncovered between individual ACFs and the diffusion law, we used an ACF inversion method originally proposed by Shusterman et al 39,40 , and later put forward in the context of anomalous diffusion studies 29,41,45 . This method allows extracting a function directly from the ACF, MSD ACF (τ), which corresponds to the mean-squared displacement of the particles as long as their diffusion is governed by a Gaussian propagator (see section 2.1).…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the discrepancy in anomalous exponent uncovered between individual ACFs and the diffusion law, we used an ACF inversion method originally proposed by Shusterman et al 39,40 , and later put forward in the context of anomalous diffusion studies 29,41,45 . This method allows extracting a function directly from the ACF, MSD ACF (τ), which corresponds to the mean-squared displacement of the particles as long as their diffusion is governed by a Gaussian propagator (see section 2.1).…”
Section: Resultsmentioning
confidence: 99%
“…S3 A). Because the cellular environment is highly crowded with a compartmentalized structure, the dynamics for receptors, even of the same type, can be highly heterogeneous (67). Observed motion in a live cell can be comprised of periods of Brownian diffusion, directed diffusion, confined diffusion, and transient immobilization, all within an individual receptor trajectory.…”
Section: Extracting Dynamic Parameters From Msdmentioning
confidence: 99%
“…26,27 However, it has to be stressed that higher values of the subdiffusion exponent were also found in both simulations and experiments. 37 Taking into consideration the results presented above a rough estimation of the percolation threshold can be done using the dependence of the exponent a on the obstacle concentration. In our model the percolation threshold corresponds to the concentration of obstacles c c z 0.37-0.38 (see the inset in Fig.…”
Section: Dynamic Behavior Near the Critical Point: The Percolationmentioning
confidence: 99%
“…16 Theoretical treatment of the motion of objects in a crowded environment also results in a subdiffusive behavior. [32][33][34][35][36][37] One should remember that similar motion could be achieved by the inuence of a geometrical connement or forces. Computer simulations showed that this subdiffusive motion in the matrix of immobile obstacles has been characterized by the exponent a located in a narrow range between 0.697 (at the percolation threshold) and 1 (ref.…”
Section: Introductionmentioning
confidence: 99%